Toward a possible trauma subtype of functional neurological disorder: impact on symptom severity and physical health - Paredes-Echeverri, Sara; Guthrie, Andrew J.; Perez, David L. (Frontiers in Psychiatry, 2022)
Background As a group, individuals with functional neurological disorder (FND) report an approximately 3-fold increase in adverse life experiences (ALEs) compared to healthy controls. In patients with FND, studies have identified a positive correlation between symptom severity and the magnitude of ALEs. While not all individuals with FND report ALEs, such findings raise the possibility of a trauma-subtype of FND. Objective This study investigated if patients with FND, with or without probable post-traumatic stress disorder (PTSD) and/or significant childhood maltreatment, differed in their symptom severity and physical health. Materials and methods Seventy-eight patients with FND were recruited (functional seizures, n = 34; functional movement disorder, n = 56). Participants completed self-report measures of symptom severity [Somatoform Dissociation Questionniare-20 (SDQ-20), Screening for Somatoform Disorders: Conversion Disorder subscale (SOMS:CD), Patient Health Questionniare-15 (PHQ-15)], physical health [Short Form Health Survey-36 (SF36-physical health)], childhood maltreatment [Childhood Trauma Questionnaire (CTQ)], and PTSD [PTSD Checklist-5 (PCL-5)]; a psychometric battery of other common predisposing vulnerabilities was also completed. To adjust for multiple comparisons, a Bonferroni correction was applied to all univariate analyses. Results Patients with FND and probable PTSD (n = 33) vs. those without probable PTSD (n = 43) had statistically significant increased scores on all symptom severity measures – as well as decreased physical health scores. In secondary post-hoc regression analyses, these findings remained significant adjusting for age, sex, race, college education, and: pathological dissociation; alexithymia; attachment styles; personality characteristics; resilience scores; functional seizures subtype; or moderate-to-severe childhood abuse and neglect scores; SOMS:CD and SDQ-20 findings also held adjusting for depression and anxiety scores. In a separate set of analyses, patients with FND and moderate-to-severe childhood abuse (n = 46) vs. those without moderate-to-severe childhood abuse (n = 32) showed statistically significant increased SDQ-20 and PHQ-15 scores; in post-hoc regressions, these findings held adjusting for demographic and other variables. Stratification by childhood neglect did not relate to symptom severity or physical health scores. Conclusion This study provides support for a possible trauma-subtype of FND. Future research should investigate the neurobiological and treatment relevance of a FND trauma-subtype, as well as continuing to delineate clinical characteristics and mechanisms in individuals with FND that lack a history of ALEs.